2017
DOI: 10.1371/journal.pone.0184378
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 alters the lateral mobility and clustering of β1-integrin receptors

Abstract: Glycoprotein receptors are influenced by myriad intermolecular interactions at the cell surface. Specific glycan structures may interact with endogenous lectins that enforce or disrupt receptor-receptor interactions. Glycoproteins bound by multivalent lectins may form extended oligomers or lattices, altering the lateral mobility of the receptor and influencing its function through endocytosis or changes in activation. In this study, we have examined the interaction of Galectin-3 (Gal-3), a human lectin, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 91 publications
1
21
0
Order By: Relevance
“…Integrins function as αβ-heterodimeric receptors to convey polarity cues from the extracellular matrix (Yu et al, 2005) and it has been previously demonstrated that β1-integrins are not exclusively localized on the basolateral surface but are also located on the apical surface of subconfluent and fully polarized MDCK cells (Praetorius and Spring, 2002;Schwimmer and Ojakian, 1995;Zuk and Matlin, 1996). We found that galectin-3 interacts with α2β1-integrin at the apical membrane domain of MDCK cells.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Integrins function as αβ-heterodimeric receptors to convey polarity cues from the extracellular matrix (Yu et al, 2005) and it has been previously demonstrated that β1-integrins are not exclusively localized on the basolateral surface but are also located on the apical surface of subconfluent and fully polarized MDCK cells (Praetorius and Spring, 2002;Schwimmer and Ojakian, 1995;Zuk and Matlin, 1996). We found that galectin-3 interacts with α2β1-integrin at the apical membrane domain of MDCK cells.…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, endogenous or externally supplied galectin-3 sorts newly synthesized as well as internalized β1-integrin to the apical cell surface. The question of whether β1-integrin can be redistributed to the apical cell surface by extracellular interaction partners has been addressed previously (Zuk and Matlin, 1996). Apical overlay of MDCK cells with the extracellular matrix component type I collagen did not stimulate delivery of additional newly synthesized integrin to apical plasma membranes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Galectin‐3 was originally discovered in 1982 as Mac‐2, cloned in 1991, and subsequently recognized as a β‐galactoside‐binding lectin . It has diverse biological functions such as regulation of cell adhesion, immunity, inflammation, and fibrosis . Its pathological role in the heart, specifically heart failure, has been discussed in detail by the excellent review here .…”
Section: Discussionmentioning
confidence: 99%
“…Galectin-3 has a high affinity for b1,6GlcNAc-branched Nglycans modified by polylactosamine consisting of b-galactoside sugars. The oligomerization of integrins by galectin-3-mediated cross-linking between the b1,6GlcNAc-branched N-glycans on integrins promotes integrin function (25,27,32). To understand why deletion of N-glycosylation suppressed the ability of b4integrin to promote cancer cell progression, we examined the relationship between galectin-3 binding to b4-integrin and cellular functions of b4-integrin.…”
Section: B4-integrin-dependent Tumor Progression Is Associated With Imentioning
confidence: 99%